2002
DOI: 10.1002/1521-3951(200201)229:2<995::aid-pssb995>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

ZnTe-Based Light-Emitting-Diodes Grown on ZnTe Substrates by Molecular Beam Epitaxy

Abstract: We have investigated the ZnTe-based material system for the application to light-emitting devices. To this end, ZnTe homoepitaxy techniques have been developed to grow high-quality epitaxial layers. The conductivity control of ZnTe and ZnMgSeTe layers have been investigated. High structural quality n-type ZnTe layers with high carrier concentration are achieved by aluminum doping. Ambipolar conductivity control of quaternary layers is achieved. Aluminum doped ZnMgSeTe layers show a net carrier concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 9 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…As a wide-gap direct bandgap II-VI compound semiconductor, ZnTe has promising prospect in the application fields of pure green light emitting diodes [1], laser diodes, terahertz emissions [2] and solar cells, such as the top cell of tandem multi-junction solar cell [3] and the intermediate-band photovoltaic solar cell [4]. It is well-known that the most of wide-bandgap II-VI compounds are unipolar semiconductors, and their doping techniques have continuously attracted many attentions in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…As a wide-gap direct bandgap II-VI compound semiconductor, ZnTe has promising prospect in the application fields of pure green light emitting diodes [1], laser diodes, terahertz emissions [2] and solar cells, such as the top cell of tandem multi-junction solar cell [3] and the intermediate-band photovoltaic solar cell [4]. It is well-known that the most of wide-bandgap II-VI compounds are unipolar semiconductors, and their doping techniques have continuously attracted many attentions in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…2b. In the experimentally investigated ZnCl 2 temperature range from 220 to 270 C, all ZnMgSeTe layers showed n-type conductivity and a high carrier concentration of 9.4 Â 10 17 cm --3 was observed with ZnCl 2 cell temperature of 270 C. This carrier concentration is higher than that reported up to now in n-type ZnMgSeTe films [4]. This might be caused by the insertion of nano-cluster ZnSe : Cl into Zn 0.73 Mg 0.27 Te : Cl contributing as effective donor centres.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, carrier concentrations of 4 Â 10 18 cm --3 in Al-doped n-type ZnTe [2] and of 10 17 cm --3 in Cl-doped ZnTe [3] have been reported. However, n-type ZnMgSeTe with Mg composition of 20% showed a lower carrier concentration of 5.0 Â 10 16 cm --3 caused by difficulties of doping in wide bandgap materials [4].…”
Section: Introductionmentioning
confidence: 99%
“…This direct bandgap nature of ZnTe with a value of 2.26 eV makes it a potential candidate for the fabrication of pure-green LED devices [3][4][5][6]. Because of its high electro-optic coefficient, ZnTe also promises to be useful in the production and detection of terahertz (THz) radiation [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Though some research groups have reported the fabrication of ZnTe based devices like LEDs and terahertz detectors, most of them have preferred highly sophisticated techniques like molecular beam epitaxy (MBE), metal organic chemical vapor deposition (MOCVD), etc. to obtain ZnTe films [3][4][5][6][7][8], electrodeposition from aqueous solutions [9,10]. ZnTe is a very attractive host for optoelectronic device realizations because of its sensitivity in the green spectral region (2.26 eV).…”
Section: Introductionmentioning
confidence: 99%